BLOOD FIGURE OF RAMBON CATTLE FED FORMULATED CONCENTRATE CONTAINING SOYBEAN CAKE, POLLARD AND CORN OIL COMBINE WITH UREA XYLANASE MOLASSES CANDY - Emy Koestanti; Romziah S.; Tri Bhawono D. (UNEJ e-Proceeding, 2016)
The hemoglobin, leucocyte, and thrombocyte of blood serum figure of male Rambon cattle received silage only were not significantly(p>0.05) different when compared to Rambon cattle fed silage and supplemented with formulated concentrate which were containing soybean cake, pollard and corn oil combine with Urea Xylanase Molasses Candy. However, account number of erythrocyte and hematocrit value were higher (p<0.05) in the group male Rambon Cattle fed silage with formulated concentrate containing soybean cake, pollard, and corn oil. It was concluded that formulated concentrate containing soybean cake, pollard and corn oil when combined with Urea Xylanase Molasses Candy (UXMC) could maintain the serum blood figure of male Rambon cattle in the normal ranges (Hb: 8.7-9.3 g/dl, Leucocyte:7.87-10.97x109/L, Erythrocyte: 3.83-4.96 x1012/L, Thrombocyte: 543.00-632.00 x109/L, Hematocrit: 15.07-23.93%).